Explaining Michael Lewis: Literary Form and Behavioral Economics in ’The Undoing Project’ (2017) - Wilson, Christopher (Cadernos de Literatura Comparada, 2021)
This essay is concerned with the literary dimensions of Michael Lewis’s The Undoing Project (2016), a journalistic depiction of the famous intellectual collaboration of Amos Tversky and Daniel Kahneman. Tversky and Kahneman are the Israeli psychologists whose work provided a new theoretical understructure for what is now called “behavioral economics,” which has challenged norms of thinking that have longed presumed that consumer or business markets perform based on individuals’ rational assessment of their own self-interest. The current public perception of Lewis is to see him as the master of the so-called explainer, the newswriting mode that supposedly draws from the Anglo-American journalistic traditions of realism and “plain speaking” transparency; the explainer itself has become more prominent across media platforms (e.g. in podcasts) in the U.S. in recent decades. However, what this interpretation of Lewis’s writing overlooks, in the case of the Undoing Project, is the polyglot assemblage of literary and cultural debts Lewis mobilizes – from Charles Dickens and Mark Twain, American vaudeville and Yiddish humor, Voltaire and romantic comedy – to plot his explainer in the form of a love story. Through this literary strategy, moreover, Lewis tries to self-reflexively incorporate the theories behind behavioral economics into his own storytelling. In doing so, however, Lewis also confronts the ambiguous role that those theories play in contemporary history and, especially, U.S. political governance.